KONTRIBUSI KREATIVITAS DAN FASILITAS LABOR TERHADAP HASIL BELAJAR TEKNIK PEMROGRAMAN SISWA KELAS X TEKNIK AUDIO VIDEO SMK NEGERI 1 BUKITTINGGI - Taufik Mardatillah; Titi Sriwahyuni; Dedy Irfan Irfan (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2016)
This study aimed to determine the contribution of creativity and laboratory facilities Against learning outcomes Program Audio and Video (TAV) Class X in SMK Bukittinggi.  This study is correlational description. The technique of sample selection in this study using simple random sampling of 36 respondents in SMK Negeri 1 Bukittinggi. The data were analyzed using statistical methods of multiple regression analysis. The results of data analysis showed:1) creativity and laboratory facilities together contribute significantly to the learning outcomes of 25,70%, 2) creativity contribute significantly to the learning outcomes of 16,16% and 3) laboratory facilities contributes significantly to the success of learning outcomes of 13,83%. KeyWord :    creativity, laboratory facilities, learning outcomes.